WORLD HERITAGE SUSTAINABILITY: OMBILIN COAL MINING HERITAGE OF SAWAHLUNTO: KEBERLANJUTAN WARISAN DUNIA : OMBILIN COAL MINING HERITAGE OF SAWAHLUNTO - Riva Mairiska; Zulqayyim; Nopriyasman (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Ombilin Coal Mining Heritage of Sawahlunto (OCMHS) is a World Heritage originating from Indonesia, which was designated by UNESCO at its 42nd session in Baku, Azerbaijan. This World Heritage achievement has made Sawahlunto City known nationally and even internationally. OCMHS has extraordinary universal value that must be protected and preserved, because it represents multi-component technology starting from mines, mining towns, railways and ports that are well designed and integrated. This research uses historical methods, namely 1) Heuristics, namely looking for data that is relevant to the research; 2) Source Criticism, namely testing the truth and accuracy of the data obtained; 3) Interpretation, namely the stage of classifying data and facts, synthesizing facts, so that historical reconstruction can be carried out; 4) Historiography is a stage of writing like an academic work. In the course of 4 (four) years after the establishment of OCMHS, various problems emerged, starting with the resolution of 16 (sixteen) notes from the World Heritage secretariat that had not been fulfilled, a management body that had not yet been formed, the absence of adequate budget support, unclear distribution duties between the West Sumatra Provincial Government and the Central Government, regional governments run their own course in managing OCMHS assets. The management of the OCMHS World Heritage site is about joint efforts to harmonize and equalize frequencies. This is still a challenge and homework for the Central Government, Regional Government and various parties involved in it, with the aim of preserving OCMHS as a World Heritage.